Peran Kepemimpinan Transformatif dalam Strategi Pemberdayaan Masyarakat: Studi Kasus RW10 Villa Mutiara Cikarang, Desa Ciantra - Aprilia Dwi Aisyah; Suwandi (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This study aims to explore the role of change in leadership on strategies to empower communities to create organizations that focus on common goals. The study focuses on RW10 Villa Mutiara Cikarang Housing Complex, which has undergone significant changes in leadership style and community organization. The findings of this study indicate that a transformative, participatory, and communicative leadership style can enhance resident participation, strengthen organizational structures based on values, and promote the development of empowerment programs such as micro-enterprises, skill training, and environmental management. These changes have also led to increased social trust and a sense of community among residents. Despite challenges such as resistance and resource constraints, an open and consensus-based leadership approach has proven effective in creating a flexible and sustainable community organization. The findings of this study contribute to the development of appropriate local leadership practices in the context of community-based development.